2013
DOI: 10.1523/jneurosci.4116-12.2013
|View full text |Cite
|
Sign up to set email alerts
|

Axons Giving Rise to the Palisade Endings of Feline Extraocular Muscles Display Motor Features

Abstract: This study confirms that palisade endings originate in the EOM motor nuclei and further indicates that they are extensions of the axons supplying the muscle fiber related to the palisade. The present work excludes the possibility that they receive cholinergic trigeminal projections. These findings call into doubt the proposed proprioceptive function of palisade endings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
59
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(63 citation statements)
references
References 30 publications
(56 reference statements)
4
59
0
Order By: Relevance
“…20 These findings strongly suggest that palisade endings arise from MIF motoneurons in the EOM motor nuclei although receptors for cholinergic transmission have not been found in palisade endings so far with the exception of rabbit and rat. 10,20 Following tracer injection into the distal myotendinous junction (the region of the palisade endings), two populations of neurons have been retrogradely labeled at the periphery of the oculomotor nucleus, i.e., multipolar motor-like neurons and spindle shaped sensory-like neurons. 32 It has been suggested that the latter group are the source of palisade endings.…”
Section: Developmental Support For a Mif Motoneuronpalisade Ending Comentioning
confidence: 83%
See 2 more Smart Citations
“…20 These findings strongly suggest that palisade endings arise from MIF motoneurons in the EOM motor nuclei although receptors for cholinergic transmission have not been found in palisade endings so far with the exception of rabbit and rat. 10,20 Following tracer injection into the distal myotendinous junction (the region of the palisade endings), two populations of neurons have been retrogradely labeled at the periphery of the oculomotor nucleus, i.e., multipolar motor-like neurons and spindle shaped sensory-like neurons. 32 It has been suggested that the latter group are the source of palisade endings.…”
Section: Developmental Support For a Mif Motoneuronpalisade Ending Comentioning
confidence: 83%
“…[18][19][20] Combining anterograde tracer labeling and molecular analyses, we demonstrated that axons supplying palisade endings established several motor contacts alongside the muscle fibers in a manner equal to that of en grappe motor terminals on MIFs. 20 These findings strongly suggest that palisade endings arise from MIF motoneurons in the EOM motor nuclei although receptors for cholinergic transmission have not been found in palisade endings so far with the exception of rabbit and rat.…”
Section: Developmental Support For a Mif Motoneuronpalisade Ending Comentioning
confidence: 89%
See 1 more Smart Citation
“…Intrinsic (molecular) differences may account for the selective vulnerability of α-MNs versus γ-MNs in ALS, but other distinctions between these MN subtypes may play a role also. For example, unlike α-MNs, γ-MNs do not receive monosynaptic excitatory inputs from I A proprioceptive afferents; in this way, γ-MNs are like oculomotor neurons, another population of MNs selectively spared in ALS (33,34). Moreover, MNs in Onuf's nucleus that control defecation, micturition, and ejaculation are also preserved in ALS (35), and, as is consistent with excitatory proprioceptive inputs having a role in MN degeneration in ALS, these MNs do not receive vesicular glutamate transporter 1 (VGluT1) inputs, as shown in a caudal (L6) lumbar section of the mouse spinal cord (Fig.…”
Section: G93amentioning
confidence: 99%
“…30 Other studies, using central tracer injections in non-human primates, also support a motor function, but suggest that tendon endings and 'en grappe' terminals arise from separate neurons located around the periphery of the motor nuclei of EOMs. 32,33 Even though it cannot be precluded that myotendinous nerve endings have a sensory function, 2,34 the notion that muscle spindles represents the only structures with proprioceptive potency seem to gain growing support. 35 …”
Section: Myotendinous Nerve Endingsmentioning
confidence: 99%